2018
DOI: 10.1007/s00403-018-1859-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-related and seasonal changes in covalently bound ceramide content in forearm stratum corneum of Japanese subjects: determination of molecular species of ceramides

Abstract: The stratum corneum (SC) consists of corneocytes surrounded by a neutral lipid-enriched intercellular matrix. Ceramides represent approximately 50% of intercellular lipids, and play important roles in retaining epidermal water. The SC also contains covalently bound ceramides, which are thought to play a crucial role in the formation of lamellar structures, and are involved in maintaining skin barrier function. A previous report showed that levels of free ceramides in human SC changed with the seasons and age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…In the areas with high production of the skin sebum such as the face, a winter‐related decrease in sebum production (will be discussed further) significantly contributes to the skin barrier attenuation. Then, a reduced number of total ceramides, fatty acids, cholesterol, 62‐65 increased ratio of ceramides with shorter chains, 17 and containing unsaturated fatty acids 63 were found in winter skin in comparison with summer possibly contributing to a decreased water resistance of SC in winter 66,67 . These changes can be partly explained by often observed higher pH in winter 16,19,22,25,28,31,68 caused by the lack of the skin sebum and acidic NMF molecules from the sweat and leading to a decreased activity of lipid processing enzymes such as β‐glucocerebrosidase and acidic sphingomyelinase 69 .…”
Section: Discussionmentioning
confidence: 99%
“…In the areas with high production of the skin sebum such as the face, a winter‐related decrease in sebum production (will be discussed further) significantly contributes to the skin barrier attenuation. Then, a reduced number of total ceramides, fatty acids, cholesterol, 62‐65 increased ratio of ceramides with shorter chains, 17 and containing unsaturated fatty acids 63 were found in winter skin in comparison with summer possibly contributing to a decreased water resistance of SC in winter 66,67 . These changes can be partly explained by often observed higher pH in winter 16,19,22,25,28,31,68 caused by the lack of the skin sebum and acidic NMF molecules from the sweat and leading to a decreased activity of lipid processing enzymes such as β‐glucocerebrosidase and acidic sphingomyelinase 69 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, mass spectrometry has revealed low 12R‐LOX protein levels in photodamaged facial SC which is associated with a thinner SC and reduced CE maturation . It is likely that facial SC has reduced acyl‐ceramide linoleate levels that contribute to this reduced CE maturation , and age‐related reductions in covalently bound ceramides have been reported . However, the activity of 12R‐LOX has not been determined in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an unsaturated acyl chain is necessary for the formation of the lipid lamellar structure 63 . Importance of covalently bound ω-hydroxyceramides containing unsaturated fatty acid in maintenance and strengthening of epidermal lamellar structures are shown earlier 61 . In other previous reports, changes in not only covalently bound ω-hydroxyceramides but also epidermal ceramide profile or other lipids content are associated with skin barrier function 6 , 10 .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, dietary CAEP and GluCer increased levels of covalently bound ω-hydroxyceramides having unsaturated fatty acids than those having saturated fatty acids. Previous studies reported that covalently bound ω-hydroxyceramides containing unsaturated fatty acid were less sensitive to aging, seasonal variation, and AD-like damage compared to those containing saturated fatty acid 16,61 . The presence of an unsaturated acyl chain is necessary for the formation of the lipid lamellar structure 63 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation